2013
DOI: 10.1590/1414-431x20132785
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propofol on damage of rat intestinal epithelial cells induced by heat stress and lipopolysaccharides

Abstract: Gut-derived endotoxin and pathogenic bacteria have been proposed as important causative factors of morbidity and death during heat stroke. However, it is still unclear what kind of damage is induced by heat stress. In this study, the rat intestinal epithelial cell line (IEC-6) was treated with heat stress or a combination of heat stress and lipopolysaccharide (LPS). In addition, propofol, which plays an important role in anti-inflammation and organ protection, was applied to study its effects on cellular viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
(26 reference statements)
0
20
0
Order By: Relevance
“…IL-6 and TNF-␣ are the critical cytokines involved in inflammation, and their inhibition is regarded as a common treatment strategy for inflammation-related diseases (Locksley et al 2001;Burger et al 2006). In this study, we used LPS at a concentration of 1.0 g/mL (Tang et al 2013) to establish the LPS-induced injury IEC-6 cell inflammation model. We first found that baicalin suppresses LPSinduced apoptosis in IEC-6 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 and TNF-␣ are the critical cytokines involved in inflammation, and their inhibition is regarded as a common treatment strategy for inflammation-related diseases (Locksley et al 2001;Burger et al 2006). In this study, we used LPS at a concentration of 1.0 g/mL (Tang et al 2013) to establish the LPS-induced injury IEC-6 cell inflammation model. We first found that baicalin suppresses LPSinduced apoptosis in IEC-6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 40 different proteins have been shown to be located in TJs, including, for example, ZO-1 proteins, occludin, and claudins (Liévin-Le and Servin 2006). Previous studies have shown that damage to IECs increases the permeability of the intestinal epithelial barrier, leading to an increase in gut-derived bacterial endotoxin translocation (Tang et al 2013) as a major factor contributing to the predisposition to inflammatory diseases of the bowel (Groschwitz and Hogan 2009) and bacteriainduced diarrhea (Hodges and Gill 2010). Lipopolysaccharide (LPS), a component of the outer wall of Gram-negative bacteria, induces the barrier function by activating chemical mediators (e.g., interleukin-6 (IL-6), tumor necrosis factor-␣ (TNF-␣), and nitric oxide), injuring epithelial cells and the TJs between epithelial cells (Hu et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…8 Recognition of LPS by TLR4 leads to cellular activation and pro-inflammatory gene expression, the latter of which is thought to be responsible for the increase in apoptosis and damage in IECs observed in IBD. 8 Indeed, LPS was believed represent a robust, rapid and consistent stimulus for inducing pathological IEC apoptosis and inflammation, 5,9 thus would exacerbate the dysfunction of the epithelial barrier and further weaken the frontline defence against pathogenic bacteria. It is remarkable that IECs rather than macrophages or other lamina propria populations are found as the predominant cells expressing TLR4 in human intestinal mucosa.…”
mentioning
confidence: 99%
“…This supports our study showing higher gingival fibroblast growth following stimulation with P. gingivalis LPS. This overgrowth may be a common cell behavior in response to endotoxin stimulation or possibly a cell‐specific behavior against the harmful effect of P. gingivalis or its virulence factors, thereby preventing periodontal disease . Interestingly, cell growth was promoted by α‐tocopherol, which suggests that this molecule may play a preventive role against periodontal disease.…”
Section: Discussionmentioning
confidence: 99%